Layanan Purna Jual terhadap Kepuasan Konsumen (Studi Kasus Sepeda Motor Honda pada Bengkel Ahass PT. Mega Wahana Pesona Sengeti Muaro Jambi) - Irwan Dwi Saputra Pardede; Fachruddin Razi; Anaseputri Jamira; Yulita Febriani (Universitas Batanghari Jambi, 2023)
This study had purpose to find out how the influence of After-Sales Service on Consumer Satisfaction with a Case Study of Honda Motorcycles at the Ahass Workshop of PT. Mega Wahana Pesona Sengeti Muaro Jambi. The analysis used in this study is multiple linear regression on a sample of 100 respondents who are consumers at the Ahass workshop at the PT. Mega Wahana Pesona Sengeti Muaro Jambi. The results showed that there was a positive and significant effect of after-sales service on customer satisfaction at Ahass workshop at PT. Mega Wahana Pesona Sengeti Muaro Jambi. The company is expected to improve inventory management to ensure that the supply of accessories or spare parts does not wait too long. The company is also expected to optimize the promotion mix to improve the company's brand image. Future researchers are expected to develop research by examining other elements that are not present in this study, and not using simple models to obtain better research results.